Особенности использования неразрушающих акустических методов для прогнозирования защитных свойств комбинированных керамико-полимерных материалов - Безымянный, Юрий Георгиевич; Мазная, Александра Викторовна; Высоцкий, Андрей Николаевич; Комаров, Константин Андреевич; Талько, Оксана Викторовна (НТУ "ХПИ", 2017)
Разработана оригинальная методика оценки защитных свойств комбинированных керамико-полимерных материалов и их слоев при сопротивлении ударным нагрузкам путем адаптации импульсного метода измерения скорости распространения упругой волны. Показано целесообразность применения ударного метода воздействия на фронтальную поверхность исследуемого образца для возбуждения упругой волны с широким спектром частот. Использование методики дает возможность прогнозирования эффективности применения защитных преград разного состава.

Creation of effective protection against high-energy killers is always actual in connection with their constant improvement. One of the most prospective directions of ballistic protection is connected with the development of a combined multilayered material as a protective structure. The material consists of armored ceramics and a substrate made from polymeric composites. Elastic waves velocities are physically connected with density and elastic properties of the material, and an attenuation coefficient of an elastic wave – with its damping properties and inner structure. An original technique of evaluation of protective properties of combined ceramics-polymeric materials and their layers under shock resistance was developed by adapting the impulse method of measuring elastic wave velocity to the peculiarities of the products under study and to the problem of this investigation. Application of this technique made it possible to compare efficiency of using protective barriers of different compositions and give recommendations concerning their completing with layers of materials possessing different properties.
Peculiarities in using nondestructive acoustic methods for prognostication protective properties of combined ceramic – polymeric materials
Keywords: ударная нагрузка; метод измерения скорости; упругая волна; частота; ballistic protection; elastic waves; damping properties